Whole-Body Cryostimulation: New Insights in Thermo-Aeraulic Fields inside Chambers - Elfahem, Rim; Abbes, Boussad; Bouchet, Bastien; Murer, Sebastien; Bogard, Fabien; Moussa, Tala; Beaumont, Fabien; Polidori, Guillaume (Inventions, 2023)
(1) Background: This article presents a study that aims to provide a precise understanding of the temperature distribution within a whole-body cryostimulation (WBC) chamber, whether it is empty or occupied by one or several individuals; (2) Methods: The study employs a mixed numerical and experimental approach, utilizing simplified computational fluid dynamics (CFD) simulations and experimental analysis; (3) Results: The results reveal a non-negligible temperature difference between the setpoint and actual temperature in the middle of the cryochamber. Furthermore, it is shown that the presence of individuals inside the chamber results in both an average temperature rise and a more heterogeneous thermal behavior associated with the number of individuals present. As the number of occupants in the cryochamber increases, the magnitude of the thermal gradient (up to 10 °C) and temperature heterogeneity (up to 13%) also increase; (4) Conclusions: The results suggest that when the cryotherapy chamber is occupied by three people, it becomes necessary to extend the duration of cold exposure to obtain a dose/effect ratio and analgesic threshold equivalent to those obtained when only one person is present. The findings of this study emphasize the need for further research to establish temperature guidelines and standardize measurement methods for effective WBC treatment.
Number: 4
Keywords: CFD; inside temperature fields; thermal stratification; whole-body cryostimulation